Warwick-India-Canada (WIC) global mental health group: rationale, design and protocol - Aileen Clarke; Richard J Lilford; Sanjeev Jain; Jason Madan; Arti Bakshi; Graeme Currie; Tasneem Raja; Tom Burns; Swaran P Singh; Max Birchwood; Caroline Meyer; Mohapradeep Mohan; et al. (BMJ Open)
Introduction The primary aim of the National Institute of Health Research-funded global health research group, Warwick-India-Canada (WIC), is to reduce the burden of psychotic disorders in India. India has a large pool of undetected and untreated patients with psychosis and a treatment gap exceeding 75%. Evidence-based packages of care have been piloted, but delivery of treatments still remains a challenge. Even when patients access treatment, there is minimal to no continuity of care. The overarching ambition of WIC programme is to improve patient outcomes through (1) developing culturally tailored clinical interventions, (2) early identification and timely treatment of individuals with mental illness and (3) improving access to care by exploiting the potential of digital technologies.Methods and analysis This multicentre, multicomponent research programme, comprising five work packages and two cross-cutting themes, is being conducted at two sites in India: Schizophrenia Research Foundation, Chennai (South India) and All India Institute of Medical Sciences, New Delhi (North India). WIC will (1) develop and evaluate evidence-informed interventions for early and first-episode psychosis; (2) determine pathways of care for early psychosis; (3) investigate the efficacy and cost-effectiveness of community care models, including digital and mobile technologies; (4) develop strategies to reduce the burden of mental illnesses among youth; (5) assess the economic burden of psychosis on patients and their carers; and (6) determine the feasibility of an early intervention in psychosis programme in India.Ethics and dissemination This study was approved by the University of Warwick’s Biomedical and Scientific Research Ethics Committee (reference: REGO-2018-2208), Coventry, UK and research ethics committees of all participating organisations. Research findings will be disseminated through peer-reviewed scientific publications, presentations at learnt societies and visual media.